EUROPEAN UNION AGREEMENT IN OIL SECTOR: A SYSTEMATIC LITERATUR REVIEW (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2023)
This study aims to determine the European Union's policy on exports in the energy sector, especially the oil sector. The research method applied in this study was a systematic literature review using 579 scientific articles sourced from the Scopus database. Review articles using the Vosviewer application. The results of the study reveal that the European Union has several new policies for oil exports from several countries. The results of this study contribute to the development of a research roadmap on policies used by the European Union. A large number of palm oil industries in several countries have opened up many jobs for the surrounding community so this industry has played a major role in absorbing labor. The limitation of this research is that the articles used are only sourced from the Scopus database so the research findings cannot comprehensively describe the European Union's policy issues on oil exports. Subsequent research needs to use scientific articles sourced from other reputable international databases, such as Web of Science and Dimensions Scholars.